Anterior Lamellar Keratoplasty Using Artificial Biotransplant in Veterinary Ophthalmology - Boris V. Usha1, Vladimir I. Lutsay1, Inga M. Nityaga2, Uliyana E, Lukashina3, Evgeny V. Davidov4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The article describes a method for anterior lamellar keratoplasty with biological material from porcine smallintestine submucosa (tunica submucosa) used to replace the damaged area of the cornea. The indicationsfor surgery were deep ulcers caused by chronic irritation, septic ulcers with elements of keratomalacia,corneal sequesters, traumatic needle-shaped ulcers and xerotic ulcers in cats. Complete graft integration wasachieved in 27 eyes (77,14 %) of 35. In 8 cases (22,86 %) complications occurred. Suture failures, partial graftintegration and central thinning of the transplant were later corrected by repeated surgeries. Panophthalmitisdeveloped in one eye required its enucleation. Observating the late postoperative period showed a minimaldecrease in visual functions, which is not always possible to achieve through other surgeries.